2015
DOI: 10.1063/1.4923053
|View full text |Cite
|
Sign up to set email alerts
|

Size-efficient metamaterial absorber at low frequencies: Design, fabrication, and characterization

Abstract: Articles you may be interested inA novel ultrathin and broadband microwave metamaterial absorber J. Appl. Phys. 116, 094504 (2014); 10.1063/1.4894824Bandwidth-enhanced polarization-insensitive microwave metamaterial absorber and its equivalent circuit model Integrating non-planar metamaterials with magnetic absorbing materials to yield ultra-broadband microwave hybrid absorbers Appl. Phys. Lett.We numerically and experimentally demonstrated a metamaterial perfect absorber (MPA) in MHz region based on a planar … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 43 publications
(15 citation statements)
references
References 37 publications
0
15
0
Order By: Relevance
“…Interestingly, the ratios between thicknesses t and lattice constant a of MPA to the operation wavelength λ at 102 MHz are optimized to be only: t / λ  = 1/816 and a / λ  = 1/84. These values are the smallest among the currently-published structures212223242526272829. The nature of perfect absorption can be explained by the impedance matching theory30.…”
Section: Design Results and Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Interestingly, the ratios between thicknesses t and lattice constant a of MPA to the operation wavelength λ at 102 MHz are optimized to be only: t / λ  = 1/816 and a / λ  = 1/84. These values are the smallest among the currently-published structures212223242526272829. The nature of perfect absorption can be explained by the impedance matching theory30.…”
Section: Design Results and Discussionmentioning
confidence: 97%
“…3(a) 233233. L 1 and L 2 are the effective inductances of the top quarter of meta-surface and the via interconnect located at each quadrant of the unit cell, respectively.…”
Section: Design Results and Discussionmentioning
confidence: 99%
“…For a low‐frequency MM absorber, the unit cell size is an important factor because of a periodic configuration of a MM. Therefore, various unit cell geometry for miniaturization has been proposed in a low frequency . For instance, a snake‐shape unit cell is proposed to design MM absorbers at 2 GHz and 400 MHz .…”
Section: Introductionmentioning
confidence: 99%
“…A needlepoint‐shape MM unit cell is designed using a magnetic material at 400 MHz . A planar sandwiched metal‐dielectric‐metal unit cell is proposed to minimize the MM unit cell size at 400 MHz . The unit cell size of the MM absorber is reduced by loading lumped capacitors and vertical interconnects at 102 MHz .…”
Section: Introductionmentioning
confidence: 99%
“…With further developments, research in this area includes achieving near unity absorption characteristics for multiband, broadband frequencies maintaining polarization insensitive and ultra-thin profile. There are articles which report broadband absorption phenomenon [2][3][4][5][6]. However, on further investigations, it was found that the broadband absorption resulted from ignorance of cross-polarized reflections from the structures.…”
Section: Introductionmentioning
confidence: 99%